1999
DOI: 10.1139/y99-032
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of chilli pepper (Capsicum annuum) reduces salicylate bioavailability after oral aspirin administration in the rat

Abstract: The bioavailabilities of aspirin (acetylsalicylic acid) and of salicylic acid were studied in male Wistar rats after acute and chronic administration of a Capsicum annuum extract, containing 100 mg of capsaicin per gram. With a single administration of 100 mg/kg of the extract, aspirin blood levels remained unchanged, but salicylic acid bioavailability was reduced in 44% compared with control animals. With a single administration of 300 mg/kg of the extract, aspirin blood levels were undetectable while salicyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…This interpretation is in agreement with Cruz et al (1999), who reported a similar delay of 60 min in rat. Finally, in vitro increase of TCA levels, which was noted in humans and in rats in the presence of SA, was also observed during our in vivo investigations but did not achieve statistical significance.…”
Section: Salicylic Acidsupporting
confidence: 93%
“…This interpretation is in agreement with Cruz et al (1999), who reported a similar delay of 60 min in rat. Finally, in vitro increase of TCA levels, which was noted in humans and in rats in the presence of SA, was also observed during our in vivo investigations but did not achieve statistical significance.…”
Section: Salicylic Acidsupporting
confidence: 93%
“…The variation of the oedema volume at each time was calcu-lated as delta volume (ÁVt ¼ Vt À Vo) in mL. A delta volume versus time curve was constructed for each treatment and its area under the curve (AUC) was calculated for the period of observation (AUC 0-5 h ) using the trapezoidal method (Cruz et al 1999). Inhibition of oedema (%EI) was calculated by the equation: %EI ¼ (AUCcontrol À AUCtreat) Â 100/AUCcontrol.…”
Section: Anti-inflammatory Studiesmentioning
confidence: 99%
“…Fasted rats (12 h) were grouped randomly into four groups of six rats each and orally administered as follows: the first group with diclofenac sodium (10 mg kg À1 ) þ vehicle (0.5% Tween 80 in saline solution, 0.5 mL/100 g body weight, control group); second group with diclofenac sodium (10 mg kg À1 ) þ 30 mg kg À1 CME (30 CME group); third group with diclofenac sodium (10 mg kg À1 ) þ 100 mg kg À1 CME (100 CME group); and the fourth group with diclofenac sodium (10 mg kg À1 ) þ 300 mg kg À1 CME (300 CME group). For the determination of plasma diclofenac before (t ¼ 0 min) and after (3,6,10,15,20,30,45,60,90,120,240,480 and 600 min) the administration, whole blood samples (100 L) were taken from the cannula inserted and fixed in the caudal artery (Cruz et al 1999). The same volume of blood extracted at each time was replaced immediately after sampling with physiological isotonic saline solution to avoid any reduction in circulation volume.…”
Section: Pharmacokinetic Studiesmentioning
confidence: 99%
“…Tamarind ( Tamarindus indica ) has been shown to increase the bioavailability of aspirin 58 . Ingestion of chili pepper ( Capsicum annuum ) reduces salicylate bioavailability after ingestion of aspirin in rats 59 . Capsicum has also been shown to induce increased fibrinolytic activity and simultaneously cause hypocoagulability of blood when ingested or when retained in the mouth for a short time 60 …”
Section: Altered Coagulationmentioning
confidence: 99%
“…58 Ingestion of chili pepper (Capsicum annuum) reduces salicylate bioavailability after ingestion of aspirin in rats. 59 Capsicum has also been shown to induce increased fibrinolytic activity and simultaneously cause hypocoagulability of blood when ingested or when retained in the mouth for a short time. 60 In addition to garlic (Allium sativum), evidence exists that danshen 61,62 (Salvia miltiorrhiza), dong quai 63 (Angelica sinensis), and papaya 64 (Carica papaya) increase the INR of patients taking warfarin.…”
Section: Altered Coagulationmentioning
confidence: 99%